The role of the tribe in achieving national reconciliation - mohamed, Ashraf Suleiman Abu Bakr (Tobruk University Journal of Social and Human Sciences, 2025)
The Libyan society has undergone many changes, especially after the February 17 Revolution, where chaos prevailed and the tearing of the social fabric surfaced. This, in turn, reflects on social security, coexistence, and tolerance among members of the same community. It is well known that after the fall of the regime, many problems emerged, including the proliferation of weapons and the formation of armed groups. This resulted in a reality marked by the spread of regional and tribal conflicts, undermining social relations. Amidst these conditions and conflicts, the role of the tribe emerges in resolving these disputes and conflicts among members of the same community and achieving national reconciliation, given the important role and influence the tribe holds in Libyan society. Therefore, the general question of this paper is: What is the role of the tribe in achieving national reconciliation and maintaining the unity of society and its social relations? The research will rely on the descriptive method and use its techniques, particularly the library method, which depends on reviewing and analyzing the literature related to the topic after collecting data and information about it, then organizing and analyzing these data to derive the most important results.